KAJIAN KOTA LAYAK HUNI DI KOTA PEKANBARU - Muhamad Iqbal Hisyam; Febby Asteriani; Muhammad Sofwan; Ade Wahyudi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2023)
A livable city is a development idea that focuses on the escalation of quality of life and conflict management by integrating the value of amenities and economic viability in urban design. A study conducted by the Indonesia Association of Planners said Pekanbaru City was one the unlivable city in Indonesia in 2017, or it only achieved 57,8% and was in sixth place. This research aims to analyze the components of a livable city and provide a strategy to develop a livable city in Pekanbaru. There are 29 criteria will be examined, and in-depth interviews with experts who completely know about the livable city concepts. The analytical hierarchy process is applied to analyze the livable city components and provide the optimum strategy to enhance the livable city level. The result showed that the livable city index had improved by 60% since 2017 or increased by 2,2% over the past three years. However, the important indicators that need to be raised were cleanliness (40%), economic (46%), pedestrians (44%), and accessibility (46%). Meanwhile, urban revitalization, maintenance of public facilities, open space, security and social, economic facilities, and sanitation management have become a major focus to make Pekanbaru a livable city.